2021
DOI: 10.1007/s11077-021-09443-1
|View full text |Cite
|
Sign up to set email alerts
|

Institutional complexity traps in policy integration processes: a long-term perspective on Swiss flood risk management

Abstract: Complexity is inherent to the policy processes and to more and more domains such as environment or social policy. Complexity produces unexpected and counterintuitive effects, in particular, the phenomenon of policy regimes falling short of expectations while made by refined policies. This paper addresses this phenomenon by investigating the process of policy integration and its nonlinearities in the long run. We consider that the increase in the number of policies unexpectedly impacts the policy coherence with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…From a design perspective, it has been argued that policy integration requires that all instruments appropriately interact with each other, enabling them to potentially achieve such a goal (Briassoulis, 2017 ; Howlett & del Rio, 2015 ). Moreover, the coherence and congruence of the instruments that make up the policy mix must be preserved during implementation (Bolognesi & Pflieger, 2019 ; Bolognesi et al, 2021 ; Cejudo & Michel, 2021 ; Maor & Howlett, 2021 ).…”
Section: Defining Policy Integrationmentioning
confidence: 99%
“…From a design perspective, it has been argued that policy integration requires that all instruments appropriately interact with each other, enabling them to potentially achieve such a goal (Briassoulis, 2017 ; Howlett & del Rio, 2015 ). Moreover, the coherence and congruence of the instruments that make up the policy mix must be preserved during implementation (Bolognesi & Pflieger, 2019 ; Bolognesi et al, 2021 ; Cejudo & Michel, 2021 ; Maor & Howlett, 2021 ).…”
Section: Defining Policy Integrationmentioning
confidence: 99%
“…In the longer term, TCCs are thus likely to lead to an overall loss of policy coherence which will further hamper the formulation and implementation of integrated policies. This has been identified as an "Institutional Complexity Trap" (ICT) because policy designs get more complex without generating concrete gains in terms of policy integration at the implementation stage (Bolognesi & Nahrath, 2020;Bolognesi et al, 2021).…”
Section: Avoiding Integration Failures Throughout Implementation: a C...mentioning
confidence: 99%
“…Moreover, the Swiss federal planning policy introduced in 1979 is in direct contradiction with land ownership guarantees anchored in the Swiss Constitution since 1969. Investigating these contradictions, some scholars have concluded that land-use planning in Switzerland is a nice illustration of an "Institutional Complexity Trap" (Bolognesi et al, 2021;Nahrath, 2005;Varone & Nahrath, 2014).…”
Section: Curbing Urban Sprawl In a Federalist Countrymentioning
confidence: 99%
“…An increasing number of studies have analyzed policies and policy documents (e.g., Bolognesi et al, 2021;Metz et al, 2020;Nkiaka & Lovett, 2018) to investigate how specific issues relate to one or more policy sectors, and have related this to policy integration and similar concepts. However, few have adopted an actor-centered approach and analyzed which actors bring issues into which sectors (for exceptions, see Vogeler, 2022;Brandenberger et al, 2022;Metz & Glaus, 2019;Metz et al, 2020).…”
Section: Theorymentioning
confidence: 99%